PENDIDIKAN SPIRITUAL DALAM KITAB TUHFAH AL-MAUDŪD BI AHKĀMI AL-MAULŪD KARYA IBNU QAYYIM AL-JAUZIYYAH - Arief Rifkiawan Hamzah (Tarbawiyah Jurnal Ilmiah Pendidikan, 2018)
Tuhfah Al-Maudūd Bi Ahkāmi Al-Maulūd is one of the books of Ibn Qayyim Al-Jawziyyah which discusses different issues compared to other works. This article examines spiritual education written by Ibn Qayyim Al-Jawziyyah in his book. This study is interesting to do, since the focus of education mostly only penetrated the intellectual intelligence and emotional intelligence, while spiritual intelligence still has not received intense attention in education. Then the study of this book is still not much done in terms of spiritual education. This study is a literature study with the primary source of the book Tuhfah Al-Maudūd Bi Ahkāmi Al-Maulūd and other supporting books of Ibn Qayyim Al-Jawziyyah. The theory that the writer uses here is from Islamic education theory written by Syed Muhammad Naquib Al-Attas and Ramayulis, then about the sprititual intelligence of Ary Ginanjar Agustian and Danah Zohar-Ian Marshall. Based on the theory, Ibn Qayyim views that education is ta'dib, which represents the good of the body and the ruhaniyah. Spiritual intelligence is the first thing parents notice, from before birth until delivery. The educational environment should be designed to avoid bad images, noise, and action that could endanger the child's comfort.